2017
DOI: 10.17645/si.v5i4.1149
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Social Inclusion through Multilingual Habitus in Estonia: A Case Study of the Open School of Kalamaja and the Sakala Private School

Abstract: After the restoration of independence in 1991, Estonia continued with a parallel school system with separate public schools operating for Russian-and Estonian-speaking children. Seen as a developmental 'growing pains' of a transitional state, during the last 27 years the separate school system has contributed to infrastructural difficulties, educational injustice, and societal segregation. This article investigates the role of private schools in addressing this injustice from the analytical angle of new instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Multilingualism has a long history, but its visibility has increased recently due to factors such as globalisation and population mobility. According to the Center for Modern Languages of the Council of Europe, more than half of the world's population is bilingual or multilingual (L'nyavskiy-Ekelund & Siiner, 2017).…”
Section: Theoretical and Conceptual Frameworkmentioning
confidence: 99%
“…Multilingualism has a long history, but its visibility has increased recently due to factors such as globalisation and population mobility. According to the Center for Modern Languages of the Council of Europe, more than half of the world's population is bilingual or multilingual (L'nyavskiy-Ekelund & Siiner, 2017).…”
Section: Theoretical and Conceptual Frameworkmentioning
confidence: 99%
“…They have been organizing meetings of migrant groups with Estonians in various forms, such as ethnic cuisine cooking classes, workshops on braid-making by refugees from Africa, and lessons on various folk cultures, where Estonians can introduce their culture to the migrants in return (Saame tuttavaks n.d.). A growing body of research has demonstrated the role of language and integration policy agents other than the state in facilitating change in Estonia (L’nyavskiy-Ekelund and Siiner 2017, 98). In fact, the scholars have long understood the notion of language policy as processual, dynamic, and in motion, emerging in the course of everyday interaction (McCarty 2011, 2–3), and inferred from people’s language practices, ideologies and beliefs (Spolsky 2004, 8).…”
Section: Why Does Ethnic Segregation Persist In Estonia?mentioning
confidence: 99%
“…Even though Estonian is the sole national and official language in Estonia (Rannut 2008, 437), 1 Russian is an important linguistic resource for employees in positions that involve contact with the public (Berezkina 2017). Russian language competence is increasingly valued by Estonians with middle and high incomes (L’nyavskiy-Ekelund and Siiner 2017, 102) as it gives advantages in career growth and facilitates direct communication within the Russian culture without interpretation (Adamson and Tshuikina 2015, 210). This is why many Estonians coming to the language group meetings are young doctors, police officers, or sales managers.…”
Section: Keelegruppmentioning
confidence: 99%
“…Finally, the linguistic landscape in Estonia is at the center of the article by Svetlana L'nyavskiy-Ekelund and Maarja Siiner (2017), who analyze the system of parallel and separated schools for Russian and Estonian speaking children. Contested as a system contributing to social injustice and segregation, the example of two private schools and their linguistic practices is examined, as the schools aim to drive inclusive institutions by employing inter alia multilingual practices.…”
Section: Minority Languagesmentioning
confidence: 99%